Enhanced adherence counselling and viral load pattern amongst people living with HIV/AIDS in a Nigerian government hospital - Nnadi, Nnenna O.; Sokolo, Josephine E.; Ikakita, Yoko; Cookey, Stella N.; Chima-Iroegbu, Thelma (International Journal Of Community Medicine And Public Health, 2026)
Background: Antiretroviral therapy (ART) remains the primary treatment for Human immunodeficiency virus (HIV) infection, aiming to reduce viral replication and mortality, but this requires lifelong adherence. To achieve viral load suppression (VLS) (below 1,000 copies/ml), the World Health Organization (WHO) recommends annual VL measurements and enhanced adherence counselling (EAC). Aim of the study was to determine the prevalence of VLS following EAC amongst the virally unsuppressed PLHIV at the Rivers State University Teaching Hospital (RSUTH) and factors influencing their virology outcomes. Methods: A retrospective descriptive review of records of 330 virally unsuppressed PLHIV, aged 18 years and more, from September 2021–March 2023. Sampling method: Random sampling method of those on three comprehensive sessions of monthly EAC. Ethical approval was obtained from the RSUTH ethical committee and an informed consent received from the ART management team. Data was collated and associations analysed with statistical significance set at p-value of<0.05. Results: The prevalence of VLS after EAC3 (three sessions) was 70.9%. Highest preponderances were among females (51.5%), middle aged (73.3%), unemployed (71.1%), those on first line ART regimen (71.3%), CD4 count of <200 cells/mm3 and statistically significant levels (p-value<0.01) in those who had < five years ART (79.5%). There were also significant logistic regression scores (4.119, p=0.042 and 41.173, p=0.000, respectively) for VLS levels after EAC2 and EAC3. Conclusions: Administration of at least three sessions of EAC with VL monitoring is helpful in achieving viral suppression in PLHWA.